2022
DOI: 10.1016/j.jadr.2021.100306
|View full text |Cite
|
Sign up to set email alerts
|

Limited negative effects of the COVID-19 pandemic on mental health measures of Ghanaian university students

Abstract: Background Stress and mental health outcomes are negatively correlated among university students throughout the world. Reports of differences in stress perception by gender exist, but there is limited data on students from sub-Saharan African countries. This study describes the burden of perceived and financial stress; characterizes mood and degree of anxiety symptoms; examines stress coping mechanisms, including resilience and repetitive negative thinking (RNT); and explores how students at a Gha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
3
15
1
Order By: Relevance
“…Males were more resilient with a greater positive affect score. The same results concluded the study of Adjepong et al [ 33 ], in which female students demonstrated lower resilience scores and higher negative mood scores as well as they reported increased stress levels during the pandemic. This finding is consistent with previous work indicating that low resilience is associated with a decreased capability to deal with stress [ 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…Males were more resilient with a greater positive affect score. The same results concluded the study of Adjepong et al [ 33 ], in which female students demonstrated lower resilience scores and higher negative mood scores as well as they reported increased stress levels during the pandemic. This finding is consistent with previous work indicating that low resilience is associated with a decreased capability to deal with stress [ 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…Reasons for the discrepancy between the previous Ghanaian study and the current study are not immediately clear but might reflect differences due to COVID-19, as the present study collected data during this time period. However, Ghanaian students reported a lower incidence of increased stress due to the COVID-19 pandemic compared to students in many other countries, and the majority of respondents reported no change or reduced stress during the survey period based on our previous work [ 41 ]. Further work is needed to assess if differences in TFEQ scores truly exist among Ghanaian men and women.…”
Section: Discussionmentioning
confidence: 99%
“…While the UE and RE scores for this study are comparable to our previous work with a large multi-country student population, EE scores among the Ghanaian students in this study are approximately half of the larger population surveyed [ 45 ]. Explanations for why this might be are beyond the scope of this study; however, the majority of Ghanaian students experienced no change or reduced levels of stress and anxiety during the data collection period [ 41 ], and as we suggested earlier, EE may provide means to cope with high levels of stress. Therefore, relatively low stress levels could have reduced the likelihood that EE would be used to manage stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most commonly, each of those emotions appeared to be increased, while more than half of the students were mentioned to experience feelings of anxiety, stress, worry, irritability, fear, and difficulty relaxing (Gadi et al, 2022). A quantitative study administered in China revealed that university students classified their perceived stress and anxiety levels as moderate (Adjepong et al, 2022). Increased levels of depression, anxiety, stress, and negative affect were found by Κornilaki (2022) on university students in Greece.…”
Section: Introductionmentioning
confidence: 99%